Prevalence of occupational musculoskeletal disorders forced by telework during the covid-19 pandemic: A case study at the Universidad Nacional del Centro del Perú - H, Révolo-Acevedo Ronald; C., Solano-Aymara Juan; D., Bonilla-Mancilla Humberto; A., Barrionuevo-Incaroca Yamill; Danizza, Jauregui-Ofracio, Janette; Judy, Huamancaja-Arias; J., Quispe-Reymundo Bimael (Edelweiss Applied Science and Technology, 2025)
The shift to widespread telework during the COVID-19 pandemic has raised concerns about its potential impact on musculoskeletal health. Factors such as suboptimal home office setups, prolonged working hours, physical conditions, and COVID-19 infection can contribute to the risk of developing musculoskeletal disorders (MSDs). Therefore, the aim of this research was to analyze the emergence of MSDs due to telework combined with COVID-19 among the administrative staff of UNCP. Data were obtained through personal interviews using the Nordic Musculoskeletal Questionnaire (NMQ), supplemented with information on hours and days of computer work. Two statistical models, binary logistic regression and conditional probability (Bayes’ theorem), were applied to evaluate MSDs associated with COVID-19 and telework. The results indicated significant musculoskeletal discomfort in the shoulders, elbows, wrists, hips/legs, knees, and ankles/feet. Particularly notable was the occurrence of pain on both body hemispheres, including the shoulder (83), elbow (105), and wrist (84). While size, weight, and daily working hours appear to play important roles in understanding factors influencing MSDs during telework, the number of teleworking days per week did not significantly predict MSD prevalence. Most MSDs in different body regions showed weak or inconclusive relationships with the combination of COVID-19 and telework; however, notable exceptions were hip/leg and knee MSDs, which exhibited moderate and significant negative associations. Logistic regression and Bayes’ theorem analyses, using a 0.51 threshold, revealed positive and negative relationships, respectively, between COVID-19 status and the probability of experiencing MSDs during teleworking.